Cancer risk in relatives of patients with a primary disorder of lymphocyte cytotoxicity: a retrospective cohort study. Issue 12 (December 2015) - Löfstedt, Alexandra; Chiang, Samuel C C; Onelöv, Erik; Bryceson, Yenan T; Meeths, Marie; Henter, Jan-Inge
Summary: Background: Mutations in genes for perforin-dependent lymphocyte cytotoxicity are associated with haemophagocytic lymphohistiocytosis, a rare disease of severe hyperinflammation that typically becomes evident in early childhood. It has been suggested that individuals with hypomorphic biallelic mutations in genes associated with haemophagocytic lymphohistiocytosis are at increased risk of developing haematological malignancies. We aimed to assess whether relatives of patients with primary haemophagocytic lymphohistiocytosis (ie, heterozygous carriers of these mutated genes) were more likely to develop cancer. Methods: In this retrospective cohort study, we used a multigeneration registry to identify relatives (parents and grandparents) of 79 Swedish children (<15 years) with primary haemophagocytic lymphohistiocytosis diagnosed between 1971 and 2011. For each relative, we randomly selected eight matched individuals from the Swedish total population registry, stratified for sex, birth year, and birth region. Relatives and matched controls were cross-linked with the Swedish Cancer Registry to establish cancer incidence rate. We then calculated the incidence rate ratio between first-degree and second-degree relatives and the matched controls. Additionally, we assessed natural-killer-cell-mediated cytotoxicity in a subgroup of first-degree relatives using standard 4 h 51 Cr assay and flow cytometry quantification of the upregulation of surface CD107a. Findings: We identified 346 first-degree and second-degree relatives from 67 families (67 mothers, 66 fathers, 106 grandmothers, and 107 grandfathers) and 2768 matched controls. Median follow-up was 49 years, range 0–54 years. By death or last follow-up (Dec 31, 2012), first-degree relatives had a significantly increased incidence rate of malignancies than did controls (incidence rate per 1000 person-years 2·78 [95% CI 1·42–4·15] vs 1·56 [1·16–1·95]; incidence rate ratio 1·79 [95% CI 1·06–3·03]; p=0·030). Mothers had a particularly increased risk (incidence rate per 1000 person-years 4·43 [95% CI 1·99–6·87]vs 1·60 [1·08–2·11]; incidence rate ratio 2·78 [95% CI 1·48–5·21]; p=0·0014), whereas no difference was found between fathers and controls (1·24 [0·00–2·51] vs 1·52 [0·89–2·15]; 0·82 [0·29–2·29]; p=0·70) or between grandparents and controls (7·24 [5·44–9·04] vs 6·36 [5·70–7·03]; 1·14 [0·88–1·48]; p=0·33). Functional analysis of heterozygous carriers of mutations associated with haemophagocytic lymphohistiocytosis could not show significantly reduced lymphocyte cytotoxicity. Interpretation: Heterozygous mutations in genes associated with haemophagocytic lymphohistiocytosis might be a new risk factor for cancer. The increased risk of cancer might imply haploinsufficiency of cytotoxic lymphocyte-mediated immunosurveillance of cancer in carriers of these mutations. Our findings might support intensified screening for malignancies in relatives of patients with haemophagocytic lymphohistiocytosis. Funding: Swedish Children's Cancer Foundation, Swedish Research Council, Histiocytosis Association, Swedish Cancer Society, Swedish Cancer and Allergy Foundation, Mary Béve Foundation, Karolinska Institutet Research Foundation, Stockholm County Council (ALF-project).